PIERS Proteinuria: Relationship With Adverse Maternal and Perinatal Outcome - Payne, Beth; Magee, Laura A.; Côté, Anne-Marie; Hutcheon, Jennifer A.; Li, Jing; Kyle, Phillipa M.; Menzies, Jennifer M.; Moore, Peter; Parker, Claire; Pullar, Barbra; Dadelszen, Peter von; Walters, Barry N. (Journal of Obstetrics and Gynaecology, 2011)
To examine the ability of three different proteinuria assessment methods (urinary dipstick, spot urine protein:creatinine ratio [Pr/Cr], and 24-hour urine collection) to predict adverse pregnancy outcomes Methods: We performed a prospective multicentre cohort study, PIERS (Preeclampsia Integrated Estimate of RiSk), in seven academic tertiary maternity centres practising expectant management of preeclampsia remote from term in Canada, New Zealand, and Australia- Eligible women were those admitted with preeclampsia who had at least one antenatal proteinuria assessment by urinary dipstick, spot urine Pr/Cr ratio, and/or 24-hour urine collection Proteinuria assessment was done either visually at the bedside (by dipstick) or by hospital clinical laboratories for spot urine Pr/Cr and 24-hour urine collection- We calculated receiver operating characteristic area under the curve (95% CI) for each proteinuria method and each of the combined adverse maternal outcomes (within 48 hours) or adverse perinatal outcomes (at any time) Models with AUC ≥ 0-70 were considered of interest- Analyses were run for all women who had each type of proteinuria assessment and for a cohort of women (“ALL measures”) who had all three proteinuria assessments
Keywords: Proteinuria; Preeclampsia; Receiver operating characteristic curve; diagnostic accuracy; Competing Interests